2015
DOI: 10.4081/rt.2015.5764
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Metastasis of Triple Negative Invasive Lobular Carcinoma

Abstract: Invasive lobular carcinomas are the second most common type (5% to 15%) of invasive breast carcinomas. The most frequent sites of breast cancer metastasis are the local and distant lymph nodes, brain, lung, liver, and bones; metastasis to the gastrointestinal system, especially to the stomach, is rare. When a mass is detected in an unusual place in a patient with invasive lobular carcinoma, it should be kept in mind that such a mass may be either a second primary carcinoma or the metastasis of an invasive lobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Each case is clinically unique, as outlined in the aforementioned discussion. Although there are reported cases of triple negative lobular cancers in the literature, those cases are usually in the pleomorphic form [8,21,22] . All of our cases were negative for HER-2.…”
Section: Resultsmentioning
confidence: 99%
“…Each case is clinically unique, as outlined in the aforementioned discussion. Although there are reported cases of triple negative lobular cancers in the literature, those cases are usually in the pleomorphic form [8,21,22] . All of our cases were negative for HER-2.…”
Section: Resultsmentioning
confidence: 99%
“…The invasive lobular cancer that represents 5%-10% of primary breast cancers, frequently involves unusual metastatic sites such as the gastrointestinal tract, the gynaecological organs, the peritoneum and meninges (10)(11)(12)(13)(14) in contrast to the invasive ductal cancer that follows the more conventional metastatic pattern of breast cancers and metastasizes in liver, lungs and brain (15,16).…”
Section: Epidemiologymentioning
confidence: 99%
“…It has been documented that the invasion and metastasis of tumor cells is a major cause of mortality in patients with cancer (5). Clinical evidence has also indicated that the prognosis of gastric cancer is associated with the stage of disease at diagnosis, with early diagnosis of gastric cancer resulting in a lower incidence of metastasis and a five-year survival rate of >90% (6). Although a number of studies have focused on gastric cancer at the molecular level (7)(8)(9), the mechanism underlying the invasion and metastasis of gastric cancer remains unknown.…”
Section: Introductionmentioning
confidence: 99%